Mair 1. Andrea McGuire interviews Jacqueline Mair, Witless Bay. - McGuire, Andrea (2014)
Andrea McGuire interviews Jacqueline Mair about the writing she does in her Witless Bay shed. Part 1. 00:42 - Memories of family summer home in Witless Bay, from late 60's to 1976; 03:10 - Discusses proximity of Witless Bay to St. John's; 03:35 - Contrasts modern summer holidays with summer holidays of the 60's; Describes moving "our bikes, my mother's washing machine, the cat, the goats" to Witless Bay in Father's transport truck; Recalls childhood friends on Bear Cove's Road; 07:25 - Moving back to Witless Bay in 2008; 09:52 - Writing on walls in barn of former house in Witless Bay (Sheila Ryan's current house); writing on walls of shed in Prince Edward Island; collecting words from other people via wall writings; 10:48 - Recalls eight years living in Scotland, and expressions learned there; 12:05 - Uncertainty about direct inspiration for wall writing; 13:10 - Discussion of Joey Yard's shed writing; 14:25 - Wall writings left in foreign languages; 15:10 - Remembers collage of Newfoundland words in former Battery Hotel, St. John's; 15:40 - Commentary on personal contributions to wall writing; 16:09 - Discussion of social wall writing initiated by Sheila Ryan and interviewee's son; 16:42 - Question of whether shed writing is a "local tradition"; 17:32 - Expresses social aspect of wall writing; 18:40 - Wall writing as a preservation method; 20:36 - Wall writing as representations of celebratory moments; 23:02 - Expressions learned during years abroad in the Bahamas and Scotland; 24:20 - Writing on shed walls in Prince Edward Island, the Bahamas, Scotland, and two homes in Witless Bay; 25:07 - Wall writing as a method of self-expression; 25:25 - General interest in language; 27:00 - Discussion of Newfoundland accent; confusion with Irish accent; 27:46 - Commentary on Dictionary of Newfoundland English; 28:09 - Personal interests and hobbies